P92 Miliary tuberculosis: data from a modern case-series in the United Kingdom. (14th November 2013) - Venkatraman, N; King, T; Woltmann, G; Wiselka, MJ; Bell, D; Pareek, M
Abstract : Background: Miliary tuberculosis (mTB), a severe manifestation of TB is classically associated with a high mortality. Modern data on the management and outcomes of mTB in developed world settings are lacking. We reviewed clinico-bacteriological features of mTB cases presenting to a teaching hospital in Leicester, UK serving an ethnically diverse population. Methods: Retrospective descriptive case-series of all notified mTB cases admitted between 2007 and 2012. Results: 41 cases were identified; median age 47 years (IQR:29–65 years), 61% were male and 80.5% patients were of Indian-Subcontinent origin. 92.5% of patients were foreign-born and median time between UK arrival and diagnosis was 4 years (IQR:1–10 years). 37(90.2%) patients had an HIV test; 4 were positive (median CD4 count 60;IQR 30–140). Weight loss (87.2%) and fevers (82.9%) were the most common presenting symptoms. 30 patients (73.2%) had abnormal examination findings; predominantly respiratory (63.3%). Initial bloods were diagnostically nonspecific apart from lymphopaenia and depressed lymphocyte:monocyte ratio. All patients had radiological evidence of pulmonary miliary nodules. 28/41(68.3%) patients had neuroimaging: 14/28(50%) had neuroradiological involvement–predominantly tuberculomas (12/28–42.9%). Lumbar punctures were undertaken in 73.2% of patients but only abnormal in 5 patients (17.2%) (and only 1 with normal imaging). Overall, 16(39%) patients had evidence of CNS involvement. 32/41(78.1%) patients were culture positive (all fully-sensitive) with sputum and BAL providing the highest yield. Antituberculous therapy was commenced within a median of 1 day following hospital admission. To date, 30 patients have successfully completed treatment, 3 are still on treatment, 5 have moved away and 3(7.3%) have died. In those subjects who successfully completed therapy, the lymphocyte:monocyte ratio increased significantly (p = 0.0201). Patients who died had a longer duration between admission and commencing antituberculous treatment (median 8 days; IQR 1–16 days), than those who successfully completed treatment (median 1 day; IQR 0–3 days). Conclusions: In this developed world setting, mTB is not an uncommon presentation. Although there was a high prevalence of co-existing neurological involvement, overall mortality was low. Undertaking diagnostic procedures for culture is important and has a high yield. Early treatment may have resulted in improved outcomes and the lymphocyte:monocyte ratio may help to monitor response to treatment in miliary TB.